REVITALISING THE RURAL HOMESTAYS DESIGN TOWARDS SUSTAINABLE TOURISM IN NANCHANG - Tao Hui Juan,; Khairun Nisa Mustaffa Halabi, (Journal of Islamic, Social, Economics and Development, 2024)
This research article addresses the pressing issue of the rapid rural development of the homestay industry in Nanchang, China, and its potential impact on sustainable tourism. As urbanization continues to influence rural areas, the naturalistic way of life that attracts tourists to homestays is under threat. The study aims to determine the extent to which urbanization has affected the homestay industry in Nanchang. The significance of this study lies in its examination of the changing dynamics between rural and urban areas as resources shift, potentially altering the appeal of homestays. The research also delves into the consequences of this shift on the local economy, tourism industry, and the postmodern ideals homestays aim to promote. The research methodology includes a pilot study followed by in-depth field research, exploratory and descriptive research methods, interviews with homestay owners and guests, and observational data collection. A comprehensive literature review provides context for the study. The results reveal that naturalistic design principles positively impact sustainable tourism growth in rural Nanchang. Travelers highly value encounters with nature, and they are willing to pay a premium for homestays that incorporate naturalistic elements. These design concepts reduce ecological impact and align with environmental ideals while preserving cultural integrity.